The Influence of Students’ Vocabulary Mastery Toward Their TOEFL Reading Comprehension Achievement - Ardiyanto, Fahrur Rijal (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
The vocabulary mastery becomes a support in learning the language. Vocabulary mastery as a trigger of someone’s achievement in TOEFL. The objective of this research is to measure the influence between the students’ vocabulary mastery toward their TOEFL Reading Comprehension achievement. The method used in this research was quantitative method. The design of this research was ex post facto design. The researcher used ex post facto design of this study to give the information about vocabulary mastery and TOEFL Reading Comprehension achievement. The result showed that the higher student’s vocabulary mastery, the higher TOEFL reading comprehension student will be. The result of calculation showed that in the significance degree of 0,05 it is obtained 0,324. By comparing the value of rx1x2 = 0,573 and ‘r’table = 0,324, the researcher makes an assumption that rx1x2 is bigger than ‘r’table 0,324 < 0,573. It can be concluded that there is significant positive influence between the students’ vocabulary mastery toward TOEFL Reading Comprehension achievement at the seventh semester students of English Department at Universitas Mayjen Sungkono in academic year of 2023/2024. It is hoped that in the future vocabulary learning will be further improved so that students can learn English more easily.